Potential use of cranial morphology in identification of monozygotic twins: A preliminary study - Sharma, Neha; Rohatgi, Shipra; Puri , Pooja (Journal of Indian Academy of Forensic Medicine, 2020)
Twins occur in about 1 in 85 human birth. Monozygotic twins are thought to be genetically indistinguishable yet can show high variability in their phenotypes. This difference and variability may be attributed to the various parameters like external factors and the role of epigenetic polymorphism. This paper aims at studying the various cephalometric measurements on the lateral cephalogramsto aid the investigators in identification of identical twins. A study on ten pairs of twins lateral cephalogram was performed in order to examine the cephalometric landmarks of cranium under controlled condition. After a thorough metric analysis, it can be stated that there are considerable variations in cephalometric dimensions of monozygotic twins.